Factors Associated with Psychological Health Issues in Diploma Nursing Students: A Cross-sectional Study - Kai, Li (South East Asia Nursing Research, 2020)
Psychological health is the expression of harmonic, expression of human personality, and is often disrupted by multiple factors. The aim of this study is to assess psychological health status and its associated factors among diploma nursing students. A cross-sectional study design was employed. The sample comprised 542 nursing students attending this anonymous survey by completed The Symptom Checklist 90 questionnaire. Descriptive statistics and logistic regression analysis were attempted to analyze overall data. The positive rate of psychological symptoms of diploma nursing students is 20.9%; the total score of SCL-90 and the scores of each factor are higher than the national norm; grade, personality, number of friends, parenting style, love experience. Whether single children and physical exercise are influential main factors of the mental health status of diploma nursing students. The contribution of Emotional Intelligence and Spirituality are crucial to the acquisition of well-being, happiness and meaning in life.